Literacy strategies for grades 4-12 : reinforcing the threads of reading - Tankersley, Karen, 1952- (Association for Supervision and Curriculum Development, 2005)
These easytouse classroom reading strategies are effective with English-speaking students in grades 4-12 and with English language learners of all ages.